Identifying key issues for university practitioners of garden-based learning in Spain. - Eugenio-Gozalbo, Marcia; Pérez-López, Raquel; Tójar-Hurtado, Juan-Carlos (Routledge, 2020)
The presence of learning gardens in Spain is growing, and the current scenario is highly diverse in relation to issues such as participatory models or purposes, among others. In the context of the 1st National Meeting on organic learning gardens, we convened eight expert practitioners in a focus group. Their discourse was analyzed through content analysis, after which four categories were selected for co-occurrence analyses. The most important questions for university garden-based practitioners in the country are presented, related to actors involved, functions that gardens fulfill, strengths of these educational resources, and requirements for their consolidation.
Keywords: Ecología agrícola; Enseñanza superior; Agricultura sostenible; Huertas; Agroecology; Degrowth transition; Higher education; Organic learning gardens; Sustainability education